Anti-tumor activity of antibody drug conjugate targeting aspartate-β-hydroxylase in pancreatic ductal adenocarcinoma. (1st May 2019) - Nagaoka, Katsuya; Bai, Xuewei; Ogawa, Kosuke; Dong, Xiaoqun; Zhang, Songhua; Zhou, Yanmei; Carlson, Rolf I.; Jiang, Zhi-Gang; Fuller, Steve; Lebowitz, Michael S.; Ghanbari, Hossein; Wands, Jack R.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely aggressive malignancy with very limited treatment options. Antibody drug conjugates (ADCs) are promising cytotoxic agents capable of highly selective delivery. Aspartate-β-hydroxylase (ASPH) is a type II transmembrane protein highly expressed in PDACs (97.1%) but not normal pancreas. We investigated anti-tumor effects of an ADC guided by a human monoclonal antibody (SNS-622) against ASPH in human PDAC cell lines and derived subcutaneous (s.c.) xenograft as well as a patient-derived xenograft (PDX) murine model with spontaneous pulmonary metastasis. The cytotoxic effects exhibited by several candidate payloads linked to SNS-622 antibody targeting ASPH + PDACs were analyzed. After i.v. administration of SNS-622-emtansine (DM1) ADC, the primary PDAC tumor growth and progression (number and size of pulmonary metastases) were determined. The PDAC cell lines, s.c. and PDX tumors treated with ADC were tested for cell proliferation, cytotoxicity and apoptosis by MTS and immunohistochemistry (IHC) assays. SNS-622-DM1 construct has demonstrated optimal anti-tumor effects in vitro . In the PDX model of human PDAC, SNS-622-DM1 ADC exerted substantially inhibitory effects on tumor growth and pulmonary metastasis through attenuating proliferation and promoting apoptosis. Highlights: Antibody drug conjugate targeting pancreatic cancer. Human monoclonal antibody that targets ASPH. Anti-tumor effects on pancreatic cancer derived pulmonary metastases.